Role of endoscopy in patients with achalasia - So Young Han; Young Hoon Youn (Korean Society of Gastrointestinal Endoscopy, 2023)
Achalasia is an esophageal motility disorder characterized by impaired lower esophageal sphincter relaxation and peristalsis of the esophageal body. With the increasing prevalence of achalasia, interest in the role of endoscopy in its diagnosis, treatment, and monitoring is also growing. The major diagnostic modalities for achalasia include high-resolution manometry, esophagogastroduodenoscopy, and barium esophagography. Endoscopic assessment is important for early diagnosis to rule out diseases that mimic achalasia symptoms, such as pseudo-achalasia, esophageal cancer, esophageal webs, and eosinophilic esophagitis. The major endoscopic characteristics suggestive of achalasia include a widened esophageal lumen and food residue in the esophagus. Once diagnosed, achalasia can be treated either endoscopically or surgically. The preference for endoscopic treatment is increasing owing to its minimal invasiveness. Botulinum toxins, pneumatic balloon dilation, and peroral endoscopic myotomy (POEM) are important endoscopic treatments. Previous studies have demonstrated excellent treatment outcomes for POEM, with >95% improvement in dysphagia, making POEM the mainstay treatment option for achalasia. Several studies have reported an increased risk of esophageal cancer in patients with achalasia. However, routine endoscopic surveillance remains controversial owing to the lack of sufficient data. Further studies on surveillance methods and duration are warranted to establish concordant guidelines for the endoscopic surveillance of achalasia.